Evaluation of students involvement in physical activities in Ibadan metropolis (2010)
The study evaluated the level of involvement of students in physical activities in the city of Ibadan. Three hundred and fifty-eight (358) students and sixty-one (61) teachers were randomly selected through multi-staged sampling procedure from fifty (50) junior secondary schools in the metropolis. The teacher and student questionnaires were used to collect relevant information that were analysed with descriptive statistics and multiple regression. Findings indicate that about 70% of the students reported that physical activities are good for them. However, they do not seem to have very good knowledge of the benefits of being involved in physical exercises. Number of health periods in the school timetable in that order significatly explained students' involvement in physical activities. Non-availability of equipments and facilities, lack of textbooks, inadequate number of teachers, administrative interest and lack of funds, among others were reported by the teachers as constraints to involving students in physical activities. To improve the present standard of teaching and to achieve the expected objectives of physical and health education, it was recommended that school management should note the school factors observed to be important and those militating against involvement in this study while allocating teacher workload.